Educação permanente e gestão do trabalho no âmbito da assistência social: estudo das demandas de capacitação profissional em Manaus - AM - (:unkn) unknown (Universidade Federal do Amazonas, 2018)
This study deals with the theme of public social policy management, with specific focus on the process of work management and permanent education within the scope of the Brazilian Social Assistance policy. The purpose of this study was based on the understanding that it was necessary to reflect on the need to articulate the assumptions of the National Permanent Education Policy (PNEP / SUAS) in the Labor Management processes within the Unified Social Assistance System (SUAS). The main objective of this study was to analyze the main training demands of the Social Welfare professionals in Manaus, which are related to the development of work in Basic Social Protection and Special Social Protection (medium complexity). In order to reach this broader objective, the following specific objectives were established: 1) To discuss the guidelines of the Work Management and Permanent Education in the ambit of the SUAS; 2) To raise the difficulties of operationalization of professional actions that are most prevalent in CRAS and CREAS in Manaus; 3) Identify the main demands for professional training of CRAS and CREAS workers in Manaus. Regarding the methodological procedures, the research was developed by means of two movements of data and information collection, through two types of research: bibliographical and documentary. The method of bibliographic research was carried out to support the theoretical discussion of the research, in which the following theoretical categories were delineated: Social Assistance, Work Management and Permanent Education. In the form of documentary research, the collection of primary documentary data occurred at the State Secretariat of Social Assistance of Amazonas (SEAS), accessing a database in the Institution. On the other hand, the secondary data of the documentary research refer to the current laws and regulations of SUAS, in which the main regulatory frameworks of Labor Management and the Permanent Training Policy of SUAS (PNEP / SUAS) were consulted. In the analysis of the data an approach of quantiqualitative nature was used, from the technique of content analysis. Regarding the results, the study allowed the construction of the professional profile of the workers who work in social assistance in Manaus, revealing the demands for professional qualification in the actions of Basic Social Protection and Special Social Protection (medium complexity). Among the results, we highlight the identification of the reduced composition of the CRAS and CREAS reference teams and the existing demands regarding the management of work in the social assistance area in Manaus. In addition, the study brought the theme to the reflection, sought to list points that allow an approximation between work management and permanent education, a practice that should be improved and defended as an alternative to improve the actions developed in the scope of social assistance.
Keywords: Assistência social; Gestão do trabalho; Educação permanente; Capacitação profissional; Políticas de assistência social; CIÊNCIAS SOCIAIS APLICADAS: SERVIÇO SOCIAL